Hypoxia Promotes Dissemination of Multiple Myeloma Through Acquisition of Epithelial to Mesenchymal Transition-like Features - Azab, Abdel Kareem; Hu, Jinsong; Pitsillides, Costas; Quang, Phong; Azab, Feda; Awwad, Rana; Thompson, Brian; Maiso, Patricia; Sun, Jessica D.; Roccaro, Aldo M. (My University, 2012)
The spread of multiple myeloma (MM) involves (re)circulation into the peripheral blood and (re)entrance or homing of MM cells into new sites of the BM. Hypoxia in solid tumors was shown to promote metastasis through activation of proteins involved in the epithelial-mesenchymal transition (EMT) process. We hypothesized that MM-associated hypoxic conditions activate EMT-related proteins and promote metastasis of MM cells. In the present study, we have shown that hypoxia activates EMT-related machinery in MM cells, decreases the expression of E-cadherin, and, consequently, decreases the adhesion of MM cells to the BM and enhances egress of MM cells to the circulation. In parallel, hypoxia increased the expression of CXCR4, consequently increasing the migration and homing of circulating MM cells to new BM niches. Further studies to manipulate hypoxia to regulate tumor dissemination as a therapeutic strategy are warranted
Keywords: Blood; Multiple myeloma; Animal experimentation; Mice; Cell adhesion; Hematology; Biochemistry; Chemotaxis